Reseña de: Sebastián FABER, Exile and cultural hegemony: Spanish intellectuals in Mexico, 1939-1975, Nashville, Vanderbilt University Press, 2002 - Carrión Sánchez, Pablo Jesús (Historia del Presente, 2004)
-